Action mechanisms of small microbial volatile compounds in plants. (23rd October 2021) - Gámez-Arcas, Samuel; Baroja-Fernández, Edurne; García-Gómez, Pablo; Muñoz, Francisco José; Almagro, Goizeder; Bahaji, Abdellatif; Sánchez-López, Ángela María; Pozueta-Romero, Javier
Abstract: Microorganisms communicate with plants by exchanging chemical signals throughout the phytosphere. Before direct contact with plants occurs, beneficial microorganisms emit a plethora of volatile compounds that promote plant growth and photosynthesis as well as developmental, metabolic, transcriptional, and proteomic changes in plants. These compounds can also induce systemic drought tolerance and improve water and nutrient acquisition. Recent studies have shown that this capacity is not restricted to beneficial microbes; it also extends to phytopathogens. Plant responses to microbial volatile compounds have frequently been associated with volatile organic compounds with molecular masses ranging between ~ 45Da and 300Da. However, microorganisms also release a limited number of volatile compounds with molecular masses of less than ~45Da that react with proteins and/or act as signaling molecules. Some of these compounds promote photosynthesis and growth when exogenously applied in low concentrations. Recently, evidence has shown that small volatile compounds are important determinants of plant responses to microbial volatile emissions. However, the regulatory mechanisms involved in these responses remain poorly understood. This review summarizes current knowledge of biochemical and molecular mechanisms involved in plant growth, development, and metabolic responses to small microbial volatile compounds. Abstract : Small volatile microbial compounds can promote growth and strong metabolic changes in plants. This review summarizes current knowledge of the biochemical and molecular mechanisms involved in such plant responses.